The Effect of Local Government Characteristics on Performance of Local Government Administration - Fikri Rizki Utama; Einde Evana; Rindu Rika Gamayuni (Universitas Prasetiya Mulya, 2019)
This study aimed to obtain empirical evidence of the level of regional wealth, the level of dependence to the central government, capital expenditure contribution and legislature size on the performance of local government administration. This research used a purposive sampling method. The study sample consisted of 293 LKPD provinces, districts, municipalities in Indonesia in 2015 which have been audited by the Supreme Audit Board. The result of the research shown that the variables of legislative size had a positive and significant effect on the performance of local government administration while the level of regional wealth, dependency level to the central government and capital expenditure contribution had no significant effect on the performance of the local government.Keywords:Performance of local government, administration, level of regional wealth,dependency level to the central government, capital expenditure contribution,legislature size.*Accounting Department - Institute of Economic Science of Al-Madani, Jalan Kavling Raya Pramuka Rajabasa, Bandar Lampung, 35144, Indonesia**Accounting Department - University of Lampung, Jl. Prof. Dr. Sumantri Brojonegoro No. 1, Bandar Lampung, 35145, Indonesia. https://doi.org/10.21632/irjbs.12.2.197-208